No place like home : locations of Heimat in German cinema - Von Moltke, Johannes, 1966- (Weimar and now, 2005)
This is the first comprehensive account of Germany's most enduring film genre, the Heimatfilm, which has offered idyllic variations on the idea that "there is no place like home" since cinema's early days. Charting the development of this popular genre over the course of a century in a work informed by film studies, cultural history, and social theory, Johannes von Moltke focuses in particular on its heyday in the 1950s, a period that has been little studied.